Real‐world diagnostic testing patterns for assessment of ring sideroblasts and SF3B1 mutations in patients with newly diagnosed lower‐risk myelodysplastic syndromes. (21st November 2020) - Patel, Jay L.; Abedi, Mehrdad; Cogle, Christopher R.; Erba, Harry P.; Foucar, Kathryn; Garcia‐Manero, Guillermo; Grinblatt, David L.; Komrokji, Rami S.; Kurtin, Sandra E.; Maciejewski, Jaroslaw P.; Pollyea, Daniel A.; Revicki, Dennis A.; et al.
Abstract: Introduction: The presence of ring sideroblasts (RS) and mutation of the SF3B1 gene are diagnostic of lower‐risk (LR) myelodysplastic syndromes (MDS) and are correlated with favorable outcomes. However, information on testing and reporting in community‐based clinical settings is scarce. This study from the Connect ® MDS/AML Disease Registry aimed to compare the frequency of RS and SF3B1 reporting for patients with LR‐MDS, before and after publication of the 2016 World Health Organization (WHO) MDS classification criteria. Methods: Ring sideroblasts assessment and molecular testing data were collected from patients with LR‐MDS at enrollment in the Registry. Patients enrolled between December 2013 and the data cutoff of March 2020 were included in this analysis. Results: Among 489 patients with LR‐MDS, 434 (88.8%) underwent RS assessment; 190 were assessed prior to the 2016 WHO guidelines (Cohort A), and 244 after (Cohort B). In Cohort A, 87 (45.8%) patients had RS identified; 29 (33.3%) patients had RS < 15%, none of whom underwent molecular testing for SF3B1 . In Cohort B, 96 (39.3%) patients had RS identified; 31 (32.3%) patients had < 15% RS, with 13 undergoing molecular testing of which 10 were assessed for SF3B1 . Conclusions: In the Connect ® MDS/AML Registry, only 32% of patients with <15% RS underwent SF3B1 testing after the publication of the WHO 2016 classification criteria. There was no change in RS assessment frequency before and after publication, despite the potential impact on diagnostic subtyping and therapy selection, suggesting an unmet need for education to increase testing rates for SF3B1 mutations.